PBAT resin and production process thereof

The PBAT resin is produced by a two-step method and the introduction of epoxy and isocyanate chain extenders, which solves the problems of excessive cross-linking and crystal point of PBAT resins in the prior art, and achieves high-quality PBAT resin production and excellent mechanical properties.

CN119591848APending Publication Date: 2025-03-11CHINA CHEM DONGHUA TIANYE NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411840087.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing PBAT resins are prone to over-crosslinking when the isocyanate is added to more than 0.5%, resulting in a large number of crystal points in the product. Although the crystal points are reduced after stirring, they still cannot meet the standard of a small number of crystal points.

Method used

The PBAT resin is produced by a two-step method, and the highly active epoxy and isocyanate chain extenders are introduced. By optimizing the esterification reaction conditions and the amount of additives added, the reaction process is controlled to ensure the stability of product quality and the controllability of the production process.

Benefits of technology

It has achieved high-quality production of PBAT resin, lower carboxyl group, better hue, no blown film crystal points, excellent mechanical properties, etc., which has improved the stability of the product and the controllability of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187761680000101
    Figure BDA0005187761680000101
  • Figure BDA0005187761680000111
    Figure BDA0005187761680000111
  • Figure BDA0005187761680000121
    Figure BDA0005187761680000121
Patent Text Reader

Abstract

The invention relates to PBAT resin and a production process thereof. The invention discloses a production process of PBAT resin. The production process comprises the following steps: S10, esterification: carrying out PTA esterification and AA esterification to obtain an ester 1 and an ester 2 respectively; mixing the esterified substance 1 and the esterified substance 2, and carrying out a co-esterification reaction to obtain an esterified substance 3; s20, pre-polycondensation: carrying out a pre-polycondensation reaction on the ester 3 and a catalyst to obtain a prepolymer; s30, final polycondensation: carrying out final polycondensation reaction on the prepolymer and a chain extender 1 to obtain a final polymer; and S40, carrying out a chain extension reaction on the final polymer and a chain extender 2, and extruding to obtain the PBAT resin. According to the PBAT resin and the production process thereof disclosed by the invention, the PBAT resin is produced by adopting a two-step method, and the chain extender which is relatively high in activity and easy to participate in polyester reaction is introduced, so that the quality stability of the product and the controllability of the production process are improved, and meanwhile, the process time is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polyester synthesis, and in particular relates to a PBAT resin and a production process thereof. Background Art

[0002] PBAT resin is a copolymer of butylene adipate and butylene terephthalate, which has the characteristics of both PBA and PBT, and has good ductility and elongation at break, as well as good heat resistance and impact resistance. In addition, it has excellent biodegradability and is one of the most active biodegradable materials in the current biodegradable plastic research and the best market application. It is widely used in film bags, ground films, textiles, foaming, injection molding and other fields.

[0003] Prior art CN 107474230A "A PBAT resin and its preparation method" adds a small amount of isocyanate to the PBAT resin and controls the content of isocyanate within the range of 0.61%-0.75%, which can improve the viscosity of the PBAT resin while ensuring the stability of the film blowing and ensuring that it will not be over-crosslinked. The resin has significantly improved film blowing properties. When the film is blown at a higher speed, the film material has good film forming properties, and there will be no holes and crystal points, ensuring the continuity of the film blowing production. During the processing, the patent stops stirring after the final shrinkage is completed, and then adds isocyanate to react for 5-30 minutes, and fills the reactor with high-purity nitrogen, presses the resin out of the reactor, granulates, and obtains PBAT resin. However, in actual practice, it is found that if the amount of isocyanate added exceeds 0.5% and is not stirred, the product will be over-crosslinked and obvious agglomeration will occur, and a large number of crystal points will be produced in the film blowing. If stirred, the product crystal points will be reduced to a certain extent, but it still cannot reach the standard of a small number of crystal points.

[0004] In view of this, the present invention proposes a new PBAT resin and a production process thereof, optimizes the one-step production process, and introduces additives to improve product stability and product quality. Summary of the invention

[0005] The object of the present invention is to provide a production process of PBAT resin, which adopts a two-step method to produce PBAT resin and introduces a chain extender with high activity and easy to participate in polyester reaction, thereby improving the stability of product quality and the controllability of the production process, and shortening the process time.

[0006] In order to achieve the above purpose, the technical solution adopted is:

[0007] A production process of PBAT resin comprises the following steps:

[0008] S10 esterification: esterification product 1 and esterification product 2 are obtained by PTA esterification and AA esterification respectively; the esterification product 1 and esterification product 2 are mixed and subjected to co-esterification reaction to obtain esterification product 3;

[0009] S20 pre-polycondensation: subjecting the esterified product 3 and the catalyst 1 to a pre-polycondensation reaction to obtain a prepolymer;

[0010] S30 final polycondensation: subjecting the prepolymer and the chain extender 1 to a final polycondensation reaction to obtain a final polymer;

[0011] S40: subjecting the final polymer and the chain extender 2 to a chain extension reaction, and then extruding to obtain the PBAT resin.

[0012] Furthermore, in the step S10, the PTA esterification process is as follows: terephthalic acid, 1,4-butanediol, and catalyst 1 are mixed, and then subjected to esterification reaction to obtain ester 1; the molar ratio of terephthalic acid to 1,4-butanediol is 1:1.8-2.4;

[0013] The AA esterification process is as follows: adipic acid, 1,4-butanediol and catalyst 1 are mixed, and then esterification reaction is performed to obtain ester 2; the molar ratio of adipic acid to 1,4-butanediol is 1:1.6-2.0.

[0014] Furthermore, the temperature of the esterification reaction in the PTA esterification process is 225-245°C, the time is 4-5h, and the pressure is 60-80kpa;

[0015] The esterification reaction temperature during the AA esterification process is 190-210°C, the time is 3-5h, and the pressure is 80kpa-normal pressure;

[0016] The co-esterification reaction is carried out at a temperature of 235-245° C., a time of 2-4 hours, and a pressure of 60-80 kPa.

[0017] Furthermore, in the PTA esterification process, the carboxyl group of the esterified product 1 is less than 200 mol / t, and the degree of polymerization of the reaction is 3-5;

[0018] In the AA esterification process, the carboxyl group of the esterified product 2 is less than 300 mol / t, and the degree of polymerization is 2-4;

[0019] During the co-esterification reaction, the carboxyl group of the esterified product 3 is less than 100 mol / t, and the degree of polymerization is 8-10.

[0020] Furthermore, the catalyst 1 is tetrabutyl titanate;

[0021] The chain extender 1 is an epoxy chain extender;

[0022] The chain extender 2 is an isocyanate chain extender.

[0023] Furthermore, the amount of catalyst 1 added is 1000-3000ppm based on the mass of PBAT resin;

[0024] In the step S30, the amount of chain extender 1 added is 1000-3000 ppm of the mass of PBAT resin;

[0025] In the step S40, the amount of chain extender 2 added is 2000-4000 ppm of the mass of the PBAT resin.

[0026] Furthermore, in the step S20, the pre-polycondensation reaction is carried out at a temperature of 235-245°C, a time of 3-5h, and a pressure of 1-3kPa;

[0027] In the step S30, the temperature of the final polycondensation reaction is 235-245°C, the time is 4-6h, and the vacuum degree is less than 50pa;

[0028] In the step S40, the temperature of the chain extension reaction is 220-240° C., the time is 0.2-0.4 h, and the vacuum degree is less than 50 Pa.

[0029] Furthermore, the carboxyl group of the prepolymer is less than 50 mol / t, the viscosity is 0.2-0.4 dl / g, and the degree of polymerization of the pre-polycondensation reaction is 30-50;

[0030] The carboxyl group of the final polymer is less than 20 mol / t, the viscosity is 1.0-1.1 dl / g, and the degree of polymerization of the final polycondensation reaction is 300-400;

[0031] The polymerization degree of the chain extension reaction is 400-500.

[0032] Another object of the present invention is to provide a PBAT resin prepared by the above-mentioned production process, which has the advantages of lower carboxyl groups, better hue, no blown film crystal points, and excellent mechanical properties.

[0033] In order to achieve the above purpose, the technical solution adopted is:

[0034] A PBAT resin is prepared using the above production process.

[0035] Furthermore, the carboxyl group of the PBAT resin is less than 15 mol / t and the viscosity is 1.5-1.6 dl / g.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The technical solution of the present invention controls the reaction process by optimizing the one-step production process and simultaneously introducing different types of chain extenders such as epoxides and isocyanates that are highly active and easy to participate in polyester reactions, thereby effectively ensuring the stability of product discharge, reducing the risk of waste discharge during the synthesis process, and effectively improving multiple product indicators, such as lower carboxyl groups, better hue, no film blowing crystal points, and excellent mechanical properties. DETAILED DESCRIPTION

[0038] In order to further illustrate the PBAT resin and its production process of the present invention and achieve the intended purpose of the invention, the following is a detailed description of the PBAT resin and its production process according to the present invention, its specific implementation, structure, characteristics and efficacy, in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0039] The following will further introduce a PBAT resin and its production process of the present invention in detail in conjunction with specific embodiments:

[0040] The present invention provides a PBAT resin and a production process thereof, optimizes a one-step production process, controls the process in the PBAT synthesis process, ensures that the process in each stage of the reaction and the amount of additives added can achieve the expected reaction effect, and finally smoothly produces a PBAT resin product with good product hue, low carboxyl content, strong hydrolysis resistance, high tensile strength and elongation at break, good film tearing performance, stable film blowing and no crystal points.

[0041] The technical solution of the present invention is:

[0042] A production process of PBAT resin comprises the following steps:

[0043] S10 esterification: esterification product 1 and esterification product 2 are obtained by PTA esterification and AA esterification respectively; the esterification product 1 and esterification product 2 are mixed and subjected to co-esterification reaction to obtain esterification product 3;

[0044] S20 pre-polycondensation: subjecting the esterified product 3 and the catalyst 1 to a pre-polycondensation reaction to obtain a prepolymer;

[0045] S30 final polycondensation: subjecting the prepolymer and the chain extender 1 to a final polycondensation reaction to obtain a final polymer;

[0046] S40: subjecting the final polymer and the chain extender 2 to a chain extension reaction, and then extruding to obtain the PBAT resin.

[0047] Preferably, in step S10, the PTA esterification process is as follows: terephthalic acid, 1,4-butanediol and catalyst 1 are mixed, and then esterification reaction is performed to obtain ester 1; the molar ratio of terephthalic acid to 1,4-butanediol is 1:1.8-2.4;

[0048] The AA esterification process is as follows: adipic acid, 1,4-butanediol and catalyst 1 are mixed, and then esterification reaction is performed to obtain ester 2; the molar ratio of adipic acid to 1,4-butanediol is 1:1.6-2.0.

[0049] Furthermore, the temperature of the esterification reaction in the PTA esterification process is 225-245°C, the time is 4-5h, and the pressure is 60-80kpa;

[0050] The esterification reaction temperature during the AA esterification process is 190-210°C, the time is 3-5h, and the pressure is 80kpa-normal pressure;

[0051] The co-esterification reaction is carried out at a temperature of 235-245° C., a time of 2-4 hours, and a pressure of 60-80 kPa.

[0052] Preferably, in the PTA esterification process, the carboxyl group of the esterified product 1 is less than 200 mol / t, and the degree of polymerization is 3-5;

[0053] In the AA esterification process, the carboxyl group of the esterified product 2 is less than 300 mol / t, and the degree of polymerization is 2-4;

[0054] During the co-esterification reaction, the carboxyl group of the esterified product 3 is less than 100 mol / t, and the degree of polymerization is 8-10.

[0055] In the above technical scheme, the requirements for the degree of polymerization of the esterification reaction and the carboxyl group of the product are to ensure that each stage of the reaction is fully completed and to avoid insufficient waste discharge caused by incomplete reaction.

[0056] Preferably, the catalyst 1 is tetrabutyl titanate;

[0057] The chain extender 1 is an epoxy chain extender;

[0058] The chain extender 2 is an isocyanate chain extender.

[0059] Further preferably, the amount of catalyst 1 added is 1000-3000ppm based on the mass of PBAT resin;

[0060] In the step S30, the amount of chain extender 1 added is 1000-3000 ppm of the mass of PBAT resin;

[0061] In the step S40, the amount of chain extender 2 added is 2000-4000 ppm of the mass of the PBAT resin.

[0062] In the above technical solution, the total addition amount of catalyst 1 in PTA esterification, AA esterification and pre-polycondensation reaction is 1000-3000 ppm.

[0063] Preferably, in step S20, the pre-polycondensation reaction is carried out at a temperature of 235-245°C, for a time of 3-5h, and at a pressure of 1-3kPa;

[0064] In the step S30, the temperature of the final polycondensation reaction is 235-245°C, the time is 4-6h, and the vacuum degree is less than 50pa;

[0065] In the step S40, the temperature of the chain extension reaction is 220-240° C., the time is 0.2-0.4 h, and the vacuum degree is less than 50 Pa.

[0066] Preferably, the carboxyl group of the prepolymer is less than 50 mol / t, the viscosity is 0.2-0.4 dl / g, and the degree of polymerization of the pre-polycondensation reaction is 30-50;

[0067] The carboxyl group of the final polymer is less than 20 mol / t, the viscosity is 1.0-1.1 dl / g, and the degree of polymerization of the final polycondensation reaction is 300-400;

[0068] The polymerization degree of the chain extension reaction is 400-500.

[0069] A PBAT resin is prepared using the above production process.

[0070] Preferably, the carboxyl group of the PBAT resin is less than 15 mol / t and the viscosity is 1.5-1.6 dl / g.

[0071] The catalyst 1 in the embodiment is tetrabutyl titanate, and a commercially available high-efficiency green catalyst with tetrabutyl titanate as a main component can be used.

[0072] The epoxy chain extender B in the embodiment is butanediol diglycidyl ether, and the isocyanate chain extender C is hexamethylene diisocyanate.

[0073] The raw materials not described in detail in this embodiment can be purchased from the market, and the treatments not described in detail adopt mature conventional means in the prior art and are common knowledge in the art.

[0074] Example 1.

[0075] The specific steps are as follows:

[0076] S10 Ingredients:

[0077] During the slurry preparation process of the dibasic acid terephthalic acid (PTA) and adipic acid (AA), the alcohol-acid ratio of the two dibasic acids to the diol BDO is controlled to be 1.2-1.5:1, the slurry preparation temperature is 80°C, and the stirring speed is 50Hz to ensure that the dibasic acid slurry can be fully and evenly dispersed in the diol BDO solution.

[0078] S20 esterification reaction:

[0079] (1) 3.32 kg of terephthalic acid, 3.25 kg of 1,4-butanediol (alkyd to acid ratio of 1.8:1) and 42 g of catalyst 1 (the amount of catalyst 1 added is 1000 ppm of the mass of the product PBAT resin) were added to a PTA esterification kettle to carry out an esterification reaction. The reaction time was controlled to be 4 h, the reaction temperature was 235° C., the reaction pressure was 60-80 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alkyd to acid reaction was controlled to be between 3 and 5, and an ester 1 having a carboxyl group content of less than 200 mol / t was obtained.

[0080] (2) 2.92 kg of adipic acid, 2.88 kg of 1,4-butanediol (reaction alcohol-acid ratio is 1.6:1), and 21 g of catalyst 1 (the amount of catalyst 1 added is 500 ppm of the mass of the product PBAT resin) were added to the AA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 3 h, the reaction temperature was 190° C., the reaction pressure was 90 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alcohol-acid reaction was controlled to be between 2 and 4, and an ester 2 with a carboxyl group of less than 300 mol / t was obtained.

[0081] (3) After the reaction is completed, ester 1 and ester 2 are mixed in a molar ratio of 1:1 and then co-esterification is carried out. The reaction time is controlled to be 2 h, the reaction temperature is 235 ° C, the reaction pressure is 60 kPa, and the stirring speed is 50 Hz to ensure that the co-esterification reaction can be completed. The degree of polymerization of the alcohol-acid reaction is controlled between 8-10, and the ester 3 with a carboxyl group of less than 100 mol / t is obtained.

[0082] S230 polycondensation reaction:

[0083] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, and 21g of catalyst 1 is added (the amount of catalyst 1 added is 500ppm of the mass of the product PBAT resin) to carry out pre-condensation polyreaction. The reaction time is controlled to be 3h, the reaction temperature is 235°C, the reaction pressure is gradually reduced from 60kPa to 1kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completely reacted, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0084] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor, and 84g of epoxy chain extender B (the amount of epoxy chain extender added is 2000ppm of the mass of PBAT resin) is added to promote the forward reaction. During the final shrinkage reaction, the reaction time is controlled to be 4h, the reaction temperature is 240°C, the reaction pressure is controlled within an absolute pressure of 50pa, and the stirring speed is 50Hz to ensure that the final shrinkage reaction can be completed. The degree of polymerization of the ester exchange reaction is controlled between 300-400, and the final polymer is controlled within 20mol / t and the intrinsic viscosity is controlled between 1.0-1.1dl / g.

[0085] (3) After the reaction is completed, 126g of isocyanate chain extender C is added to the final polymer (the amount of isocyanate chain extender added is 3000ppm of the mass of PBAT resin), and the final polymer is chain extended and extruded. The chain extension reaction temperature is controlled to be 235°C, the chain extension time is 0.3h, the stirring speed is 50Hz, and the reaction pressure is controlled to be within 50pa for chain extension reaction. After chain extension, the degree of polymerization of the product is controlled between 400-500. After the reaction is completed, the pellets are cut and dried to obtain a PBAT resin product with a carboxyl group controlled within 15mol / t and an intrinsic viscosity controlled between 1.5.-1.6dl / g.

[0086] Example 2.

[0087] The operation steps of Example 2 are the same as those of Example 1, except for the amount of the chain extender used.

[0088] Specifically: the amount of epoxy chain extender B added is 126g (the amount of epoxy chain extender added is 3000ppm of the mass of PBAT resin), and the amount of isocyanate chain extender C added is 126g (the amount of isocyanate chain extender added is 3000ppm of the mass of PBAT resin).

[0089] Example 3.

[0090] The operation steps of Example 3 are the same as those of Example 1, except for the amount of the chain extender used.

[0091] Specifically: the amount of epoxy chain extender B added is 168g (the amount of epoxy chain extender added is 4000ppm of the mass of PBAT resin), and the amount of isocyanate chain extender C added is 126g (the amount of isocyanate chain extender added is 3000ppm of the mass of PBAT resin).

[0092] Example 4.

[0093] The operation steps of Example 4 are the same as those of Example 1, except for the amount of the chain extender used.

[0094] Specifically: the amount of epoxy chain extender B added is 126g (the amount of epoxy chain extender added is 3000ppm of the mass of PBAT resin), and the amount of isocyanate chain extender C added is 84g (the amount of isocyanate chain extender added is 2000ppm of the mass of PBAT resin).

[0095] Example 5.

[0096] The operation steps of Example 5 are the same as those of Example 1, except for the amount of the chain extender used.

[0097] Specifically: the amount of epoxy chain extender B added is 126g (the amount of epoxy chain extender added is 3000ppm of the mass of PBAT resin), and the amount of isocyanate chain extender C added is 168g (the amount of isocyanate chain extender added is 4000ppm of the mass of PBAT resin).

[0098] Comparative Example 1.

[0099] The specific steps are as follows:

[0100] S10 esterification reaction: The operation steps are the same as those of the S10 esterification reaction in Example 1.

[0101] S20 polycondensation reaction:

[0102] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, 21g of catalyst 1 is added, and a pre-condensation reaction is carried out. The reaction time is controlled to be 3h, the reaction temperature is 235°C, the reaction pressure is gradually reduced from 60kPa to 1kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completed, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0103] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor, and 126g of epoxy chain extender B (the amount of epoxy chain extender added is 3000ppm of the mass of PBAT resin) is added to promote the forward reaction. During the final shrinkage reaction, the reaction time is controlled to be 4h, the reaction temperature is 240°C, the reaction pressure is controlled within an absolute pressure of 50pa, and the stirring speed is 50Hz to ensure that the final shrinkage reaction can be completed. After the reaction is completed, the PBAT resin product is obtained. Finally, the pellets are cut and dried.

[0104] Comparative Example 2.

[0105] The specific steps are as follows:

[0106] S10 esterification reaction: The operation steps are the same as those of the S10 esterification reaction in Example 1.

[0107] S20 polycondensation reaction:

[0108] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, 21g of catalyst 1 is added, and a pre-condensation reaction is carried out. The reaction time is controlled to be 3h, the reaction temperature is 235°C, the reaction pressure is gradually reduced from 60kPa to 1kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completed, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0109] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor. During the final shrinkage reaction, the reaction time is controlled to be 4 hours, the reaction temperature is 240°C, the reaction pressure is controlled within an absolute pressure of 50 Pa, and the stirring speed is 50 Hz to ensure that the final shrinkage reaction can be completed to obtain the final polymer.

[0110] (3) After the reaction is completed, 126 g of isocyanate chain extender C is added to the final polymer (the amount of isocyanate chain extender added is 3000 ppm of the mass of PBAT resin) to extend the final polymer and extrude it to obtain a PBAT resin product. Finally, pelletize and dry.

[0111] Comparative Example 3: One-step method

[0112] The specific steps are as follows:

[0113] S10 esterification reaction: The operation steps are the same as those of the S10 esterification reaction in Example 1.

[0114] S20 polycondensation reaction:

[0115] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, 21g of catalyst 1 is added, and a pre-condensation reaction is carried out. The reaction time is controlled to be 3h, the reaction temperature is 235°C, the reaction pressure is gradually reduced from 60kPa to 1kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completed, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0116] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor. During the final shrinkage reaction, the reaction time is controlled to be 4 hours, the reaction temperature is 240°C, the reaction pressure is controlled within an absolute pressure of 50 Pa, and the stirring speed is 50 Hz to ensure that the final shrinkage reaction can be completed and the final polymer is continuously reacted to obtain the PBAT resin product. Finally, the pellets are cut and dried.

[0117] Example 6.

[0118] The PBAT resins prepared in Examples 1-5 and Comparative Examples 1-3 were tested for relevant indicators such as viscosity, hue, melt index, melting point, carboxyl group, and mechanical properties.

[0119] In the present invention, the intrinsic viscosity, hue melt index, melting point, carboxyl group, mechanical properties, etc. of the polyester are tested by the following methods:

[0120] (1) Intrinsic viscosity: measured with an Ubbelohde viscometer at 25°C using a phenol-tetrachloroethane mixture as solvent;

[0121] (2) Hue: After the pellet sample was treated at 135°C for 1 hour, its Hunter L value (brightness), a value (red-green hue) and b value (yellow-blue hue) were measured using a BYK Gardner color-view automatic colorimeter. The higher the L value, the greater the brightness; the higher the b value, the yellower the polyester chips. For the present invention, it is desirable to pursue a high L value and a low b value;

[0122] (3) Melt index: measured at 250°C and 2.16 kg using an Instron CEAST MF20 melt flow rate tester.

[0123] (4) Melting point: The melting point was measured using a Shimadzu DSC-60Plus differential scanning calorimeter at a heating rate of 20°C / min.

[0124] (5) Carboxyl: The mass ratio of o-cresol to chloroform was 7:3 as the mixed solvent and potassium hydroxide-benzyl alcohol was used as the titrant for determination by volumetric titration.

[0125] (6) Mechanical properties: The specimens were injection molded into Type IA strips by an injection molding machine. The tensile strength and elongation at break were tested at a tensile speed of 50 mm / min. The cantilever beam notch impact test was performed by cutting a right-angle notch on the strips.

[0126] The test results are shown in Table 1.

[0127] Table 1 PBAT resin product properties

[0128]

[0129]

[0130] From Table 1, we can see the following points:

[0131] (1) When the total reaction time is kept constant, as the amount of epoxy chain extender and isocyanate chain extender added increases, the melt index of the product tends to decrease, the viscosity tends to increase, and the mechanical properties tend to decrease. The carboxyl group of the product is negatively correlated with the amount of epoxy chain extender added.

[0132] (2) The front-end reaction process is controlled to remain unchanged. As the amount of epoxy chain extender and isocyanate chain extender added decreases, the total reaction time of the product becomes longer, and a certain degree of thermal degradation will occur during the reaction process, resulting in an increase in the carboxyl group of the product, a deterioration in the color value, and the product melt index and viscosity are difficult to meet the national standard requirements.

[0133] (3) The changes in the melt index of different products after high temperature aging tests show that as the amount of epoxy chain extender and isocyanate chain extender added increases, the melt index of the product is lower, the change in the melt index after aging is smaller, the product has stronger high temperature resistance and higher thermal stability

[0134] Example 7.

[0135] The operation steps of Example 7 are the same as those of Example 2, except that the alcohol-acid ratio of the PTA esterification reaction is different.

[0136] Specifically: 3.32 kg terephthalic acid and 2.88 kg 1,4-butanediol (alcohol-acid ratio of 1.6:1) were added into the PTA esterification kettle.

[0137] Example 8.

[0138] The operation steps of Example 8 are the same as those of Example 2, except that the alcohol-acid ratio of the PTA esterification reaction is different.

[0139] Specifically: 3.32 kg terephthalic acid and 3.6 kg 1,4-butanediol (alcohol-acid ratio is 2:1) were added into the PTA esterification kettle.

[0140] Example 9.

[0141] The operation steps of Example 9 are the same as those of Example 2, except that the alcohol-acid ratio of the PTA esterification reaction is different.

[0142] Specifically: 3.32 kg terephthalic acid and 3.97 kg 1,4-butanediol (alcohol-acid ratio of 2.2:1) were added into the PTA esterification kettle.

[0143] Example 10.

[0144] The operation steps of Example 10 are the same as those of Example 2, except that the alcohol-acid ratio of the PTA esterification reaction is different.

[0145] Specifically: 3.32 kg of terephthalic acid and 4.33 kg of 1,4-butanediol (alcohol-acid ratio of 2.4:1) were added into the PTA esterification kettle.

[0146] Example 11.

[0147] The PBAT resins prepared in Examples 2 and 7-10 were tested for viscosity, hue, melt index, melting point, carboxyl group, mechanical properties and other related indicators, and the testing method was the same as that in Example 6.

[0148] The test results are shown in Table 2.

[0149] Table 2 PBAT resin product performance and BDO consumption

[0150]

[0151] As shown in Table 2, with the continuous increase of the alkyd-acid ratio, the product indicators have not been significantly improved, but the BDO consumption has increased significantly. The alkyd-acid ratio of 1.8:1 and 1.6:1 has the same BDO consumption, but the alkyd-acid ratio of 1.8:1 is better in terms of product indicators. Considering the economy and product indicators, the alkyd-acid ratio of 1.8:1 is selected as the optimal ratio. The change of the alkyd-acid ratio of AA has the same phenomenon as that of PTA.

[0152] Example 12.

[0153] The specific steps are as follows:

[0154] S10 Ingredients:

[0155] During the slurry preparation process of the dibasic acid terephthalic acid (PTA) and adipic acid (AA), the alcohol-acid ratio of the two dibasic acids to the diol BDO was controlled to be 1.5:1, the slurry preparation temperature was 80°C, and the stirring speed was 50 Hz to ensure that the dibasic acid slurry could be fully and evenly dispersed in the diol BDO solution.

[0156] S20 esterification reaction:

[0157] (1) 3.32 kg of terephthalic acid, 4.33 kg of 1,4-butanediol (alcohol-acid ratio of 2.4:1) and 21 g of catalyst 1 (the amount of catalyst 1 added is 500 ppm of the mass of PBAT resin) were added to a PTA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 5 h, the reaction temperature was 225° C., the reaction pressure was 60 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alkyd-acid reaction was controlled between 3 and 5 to obtain an esterified product 1 with a carboxyl group content of less than 200 mol / t.

[0158] (2) 2.92 kg of adipic acid, 3.60 kg of 1,4-butanediol (reaction alcohol-acid ratio is 2.0:1), and 21 g of catalyst 1 (the amount of catalyst 2 added is 500 ppm of the mass of PBAT resin) were added to the AA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 4 h, the reaction temperature was 200° C., the reaction pressure was 80 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alcohol-acid reaction was controlled to be between 2 and 4, and an ester 2 with a carboxyl group content of less than 300 mol / t was obtained.

[0159] (3) After the reaction is completed, ester 1 and ester 2 are mixed in a molar ratio of 1:1 and then co-esterification is carried out. The reaction time is controlled to be 3 h, the reaction temperature is 240° C., the reaction pressure is 70 kPa, and the stirring speed is 50 Hz to ensure that the co-esterification reaction can be completed. The degree of polymerization of the alcohol-acid reaction is controlled between 8 and 10, and an ester 3 with a carboxyl group of less than 100 mol / t is obtained.

[0160] S230 polycondensation reaction:

[0161] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, 42g of catalyst 1 (the amount of catalyst 2 added is 1000ppm of the mass of PBAT resin) is added, and the pre-condensation reaction is carried out. The reaction time is controlled to be 4h, the reaction temperature is 240°C, the reaction pressure is gradually reduced from 70kPa to 2kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completely reacted, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0162] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor, and 42g of epoxy chain extender B (the amount of epoxy chain extender added is 1000ppm based on the mass of PBAT resin) is added to promote the forward reaction. During the final shrinkage reaction, the reaction time is controlled to be 6h, the reaction temperature is 235°C, the reaction pressure is controlled within an absolute pressure of 50pa, and the stirring speed is 50Hz to ensure that the final shrinkage reaction can be completed. The degree of polymerization of the ester exchange reaction is controlled between 300-400, and the final polymer is controlled within 20mol / t and the intrinsic viscosity is controlled between 1.0-1.1dl / g.

[0163] (3) After the reaction is completed, 84g of isocyanate chain extender C is added to the final polymer (the amount of isocyanate chain extender added is 2000ppm of the mass of PBAT resin), and the final polymer is chain extended and extruded. The chain extension reaction temperature is controlled to be 220°C, the chain extension time is 0.4h, the stirring speed is 50Hz, and the reaction pressure is controlled to be within 50pa for chain extension reaction. After chain extension, the degree of polymerization of the product is controlled between 400-500. After the reaction is completed, the pellets are cut and dried to obtain a PBAT resin product with a carboxyl group controlled within 15mol / t and an intrinsic viscosity controlled between 1.5.-1.6dl / g.

[0164] Example 8.

[0165] The specific steps are as follows:

[0166] S10 Ingredients:

[0167] During the slurry preparation process of the dibasic acid terephthalic acid (PTA) and adipic acid (AA), the alcohol-acid ratio of the two dibasic acids to the diol BDO was controlled to be 1.3:1, the slurry preparation temperature was 80°C, and the stirring speed was 50 Hz to ensure that the dibasic acid slurry could be fully and evenly dispersed in the diol BDO solution.

[0168] S20 esterification reaction:

[0169] (1) 3.32 kg of terephthalic acid, 3.97 kg of 1,4-butanediol (alcohol-acid ratio of 2.2:1) and 42 g of catalyst 1 (the amount of catalyst 1 added is 1000 ppm of the mass of PBAT resin) were added to a PTA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 4.5 h, the reaction temperature was 245° C., the reaction pressure was 80 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alkyd-acid reaction was controlled between 3 and 5 to obtain an esterified product 1 with a carboxyl group content of less than 200 mol / t.

[0170] (2) 2.92 kg of adipic acid, 3.25 kg of 1,4-butanediol (reaction alcohol-acid ratio is 1.8:1), and 42 g of catalyst 1 (the amount of catalyst 2 added is 1000 ppm of the mass of PBAT resin) were added to the AA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 5 h, the reaction temperature was 210° C., the reaction pressure was normal pressure, the stirring speed was 50 Hz, and the degree of polymerization of the alcohol-acid reaction was controlled to be between 2 and 4, and an ester 2 with a carboxyl group of less than 300 mol / t was obtained.

[0171] (3) After the reaction is completed, ester 1 and ester 2 are mixed in a molar ratio of 1:1 and then subjected to a co-esterification reaction. The reaction time is controlled to be 4 h, the reaction temperature is 245° C., the reaction pressure is 80 kPa, and the stirring speed is 50 Hz to ensure that the co-esterification reaction can be completed. The degree of polymerization of the alcohol-acid reaction is controlled between 8 and 10, and an ester 3 with a carboxyl group of less than 100 mol / t is obtained.

[0172] S230 polycondensation reaction:

[0173] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, 42g of catalyst 1 (the amount of catalyst 2 added is 1000ppm of the mass of PBAT resin) is added, and the pre-condensation reaction is carried out. The reaction time is controlled to be 3h, the reaction temperature is 245°C, the reaction pressure is gradually reduced from 80kPa to 3kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completed, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0174] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor, and 42g of epoxy chain extender B (the amount of epoxy chain extender added is 1000ppm based on the mass of PBAT resin) is added to promote the forward reaction. During the final shrinkage reaction, the reaction time is controlled to be 5h, the reaction temperature is 245°C, the reaction pressure is controlled within an absolute pressure of 50pa, and the stirring speed is 50Hz to ensure that the final shrinkage reaction can be completed. The degree of polymerization of the ester exchange reaction is controlled between 300-400, and the final polymer is controlled within 20mol / t of carboxyl groups and the intrinsic viscosity is controlled between 1.0-1.1dl / g.

[0175] (3) After the reaction is completed, 84g of isocyanate chain extender C is added to the final polymer (the amount of isocyanate chain extender added is 2000ppm of the mass of PBAT resin), and the final polymer is chain extended and extruded. The chain extension reaction temperature is controlled to be 240°C, the chain extension time is 0.2h, the stirring speed is 50Hz, and the reaction pressure is controlled to be within 50pa for chain extension reaction. The degree of polymerization of the ester exchange reaction of the product after chain extension is controlled between 400-500. After the reaction is completed, the pellets are cut and dried to obtain a PBAT resin product with a carboxyl group controlled within 15mol / t and an intrinsic viscosity controlled between 1.5.-1.6dl / g.

[0176] Example 10.

[0177] The specific steps are as follows:

[0178] S10 Ingredients:

[0179] During the slurry preparation process of the dibasic acid terephthalic acid (PTA) and adipic acid (AA), the alcohol-acid ratio of the two dibasic acids to the diol BDO was controlled to be 1.2:1, the slurry preparation temperature was 80°C, and the stirring speed was 50 Hz to ensure that the dibasic acid slurry could be fully and evenly dispersed in the diol BDO solution.

[0180] S20 esterification reaction:

[0181] (1) 3.32 kg of terephthalic acid, 3.61 kg of 1,4-butanediol (alkyd to acid ratio of 2.0:1) and 12.6 g of catalyst 1 (the amount of catalyst 1 added is 300 ppm of the mass of PBAT resin) were added to a PTA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 4.5 h, the reaction temperature was 242° C., the reaction pressure was 70 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alkyd to acid reaction was controlled to be between 3 and 5, and an ester 1 with a carboxyl group content of less than 200 mol / t was obtained.

[0182] (2) 2.92 kg of adipic acid, 3.06 kg of 1,4-butanediol (reaction alcohol-acid ratio is 1.7:1), and 12.6 g of catalyst 1 (the amount of catalyst 2 added is 300 ppm of the mass of PBAT resin) were added to the AA esterification kettle to carry out esterification reaction. The reaction time was controlled to be 4.5 h, the reaction temperature was 205° C., the reaction pressure was 100 kPa, the stirring speed was 50 Hz, and the degree of polymerization of the alcohol-acid reaction was controlled to be between 2 and 4, and an ester 2 with a carboxyl group content of less than 300 mol / t was obtained.

[0183] (3) After the reaction is completed, ester 1 and ester 2 are mixed in a molar ratio of 1:1 and then co-esterification is carried out. The reaction time is controlled to be 2 h, the reaction temperature is 240 ° C, the reaction pressure is 65 kPa, and the stirring speed is 50 Hz to ensure that the co-esterification reaction can be completed. The degree of polymerization of the alcohol-acid reaction is controlled between 8-10, and the ester 3 with a carboxyl group of less than 100 mol / t is obtained.

[0184] S230 polycondensation reaction:

[0185] (1) After the esterification reaction is completed, the esterified product 3 is introduced into the pre-condensation reactor, 16.8g of catalyst 1 (the amount of catalyst 2 added is 400ppm of the mass of PBAT resin) is added, and the pre-condensation reaction is carried out. The reaction time is controlled to be 5h, the reaction temperature is 243°C, the reaction pressure is gradually reduced from 65kPa to 1kPa from top to bottom, the stirring speed is 50Hz, and the polymerization degree of the ester exchange reaction is controlled between 30-50 to ensure that the pre-condensation reaction can be completely reacted, and a prepolymer with a carboxyl group controlled within 50mol / t and a product intrinsic viscosity controlled between 0.2-0.4dl / g is obtained.

[0186] (2) After the pre-shrinkage reaction is completed, the prepolymer is introduced into the final shrinkage reactor, and 63g of epoxy chain extender B (the amount of epoxy chain extender added is 1500ppm based on the mass of PBAT resin) is added to promote the forward reaction. During the final shrinkage reaction, the reaction time is controlled to be 4h, the reaction temperature is 245°C, the reaction pressure is controlled within an absolute pressure of 50pa, and the stirring speed is 50Hz to ensure that the final shrinkage reaction can be completed. The degree of polymerization of the ester exchange reaction is controlled between 300-400, and the final polymer is controlled within 20mol / t and the intrinsic viscosity is controlled between 1.0-1.1dl / g.

[0187] (3) After the reaction is completed, 126g of isocyanate chain extender C is added to the final polymer (the amount of isocyanate chain extender added is 3000ppm of the mass of PBAT resin), and the final polymer is chain extended and extruded. The chain extension reaction temperature is controlled to be 230°C, the chain extension time is 0.3h, the stirring speed is 50Hz, and the reaction pressure is controlled to be within 50pa for chain extension reaction. After chain extension, the polymerization degree of the product transesterification reaction is controlled between 400-500. After the reaction is completed, the pellets are cut and dried to obtain a PBAT resin product with a carboxyl group controlled within 15mol / t and an intrinsic viscosity controlled between 1.5.-1.6dl / g.

[0188] It can be seen from the embodiments of the present invention that the PBAT resin and its production process provided by the present invention introduce different types of chain extenders such as epoxides and isocyanates with high activity and easy to participate in polyester reactions during the reaction process to promote the forward progress of the reaction, reduce the residence time of the reaction, and reduce the influence of thermal degradation and thermal oxidation degradation on the reaction during the reaction process, thereby improving the stability of product quality and the controllability of the production process.

[0189] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.

Claims

1. A production process of PBAT resin, characterized in that: The following steps are involved: S10 esterification: esterification product 1 and esterification product 2 are obtained by PTA esterification and AA esterification respectively; the esterification product 1 and esterification product 2 are mixed and subjected to co-esterification reaction to obtain esterification product 3; S20 pre-polycondensation: subjecting the esterified product 3 and the catalyst 1 to a pre-polycondensation reaction to obtain a prepolymer; S30 final polycondensation: subjecting the prepolymer and the chain extender 1 to a final polycondensation reaction to obtain a final polymer; S40: subjecting the final polymer and the chain extender 2 to a chain extension reaction, and then extruding to obtain the PBAT resin.

2. The production process according to claim 1, characterized in that: In the step S10, the PTA esterification process is as follows: terephthalic acid, 1,4-butanediol and catalyst 1 are mixed and then subjected to esterification reaction to obtain ester 1; the molar ratio of terephthalic acid to 1,4-butanediol is 1:1.8-2.4; The AA esterification process is as follows: adipic acid, 1,4-butanediol and catalyst 1 are mixed, and then esterification reaction is performed to obtain ester 2; the molar ratio of adipic acid to 1,4-butanediol is 1:1.6-2.

0.

3. The production process according to claim 1, characterized in that: The temperature of the esterification reaction in the PTA esterification process is 225-245°C, the time is 4-5h, and the pressure is 60-80kpa; The esterification reaction temperature during the AA esterification process is 190-210°C, the time is 3-5h, and the pressure is 80kpa-normal pressure; The co-esterification reaction is carried out at a temperature of 235-245° C., a time of 2-4 hours, and a pressure of 60-80 kPa.

4. The production process according to claim 1, characterized in that: In the PTA esterification process, the carboxyl group of the esterified product 1 is less than 200 mol / t, and the degree of polymerization is 3-5; In the AA esterification process, the carboxyl group of the esterified product 2 is less than 300 mol / t, and the degree of polymerization of the reaction is 2-4; During the co-esterification reaction, the carboxyl group of the esterified product 3 is less than 100 mol / t, and the degree of polymerization is 8-10.

5. The production process according to claim 1, characterized in that: The catalyst 1 is tetrabutyl titanate; The chain extender 1 is an epoxy chain extender; The chain extender 2 is an isocyanate chain extender.

6. The production process according to claim 2, characterized in that: The amount of catalyst 1 added is 1000-3000ppm based on the mass of PBAT resin; In the step S30, the amount of chain extender 1 added is 1000-3000 ppm of the mass of PBAT resin; In the step S40, the amount of chain extender 2 added is 2000-4000 ppm of the mass of the PBAT resin.

7. The production process according to claim 1, characterized in that: In the step S20, the pre-polycondensation reaction is carried out at a temperature of 235-245°C, a time of 3-5h, and a pressure of 1-3kpa; In the step S30, the temperature of the final polycondensation reaction is 235-245°C, the time is 4-6h, and the vacuum degree is less than 50pa; In the step S40, the temperature of the chain extension reaction is 220-240° C., the time is 0.2-0.4 h, and the vacuum degree is less than 50 Pa.

8. The production process according to claim 1, characterized in that: The carboxyl group of the prepolymer is less than 50 mol / t, the viscosity is 0.2-0.4 dl / g, and the degree of polymerization of the pre-polycondensation reaction is 30-50; The carboxyl group of the final polymer is less than 20 mol / t, the viscosity is 1.0-1.1 dl / g, and the degree of polymerization of the final polycondensation reaction is 300-400; The polymerization degree of the chain extension reaction is 400-500.

9. A PBAT resin, characterized in that: The invention is prepared by the production process described in any one of claims 1 to 9.

10. The PBAT resin according to claim 1, characterized in that: The carboxyl group of the PBAT resin is less than 15 mol / t and the viscosity is 1.5-1.6 dl / g.

Citation Information

Patent Citations

  • PBAT resin and preparation method thereof

    CN107474230A

Cited By

  • A rare earth-titanium bimetallic nanostructure catalyst, a preparation method and application thereof

    CN120535734B